Application of Next-Generation Sequencing Following Tandem Mass Spectrometry to Expand Newborn Screening for Inborn Errors of Metabolism: A Multicenter Study - Yang, Yuqi; Wang, Leilei; Wang, Benjing; Liu, Shuang; Yu, Bin; Wang, Ting (Frontiers in Genetics, 2019)
This study explored the effectiveness of expanding newborn screening (NBS) by tandem mass spectrometry (TMS) and gene diagnosis by next-generation sequencing (NGS). First, we described the characteristics of gene variants in Jiangsu Province. We collected clinical data from three NBS centres. All infants followed a unified screening and diagnosis process. After obtaining informed consent, dried blood spots (DBSs) were collected and analysed by TMS. If the results fell outside of the cut-off value, repeat analysis was performed. If the re-test results remained abnormal, the infant was recalled for further assessment. We performed targeted sequencing using the extended edition panel of inborn errors of metabolism (IEM) to detect 306 genes that were then subjected to massively parallel sequencing using the Illumina HiSeq 2500 platform. A total of 536,008 babies underwent NBS by TMS in three NBS centres. In total, 194 cases were eventually diagnosed with various types of inherited metabolic diseases, with an overall incidence of 1/2763. There were 23 types of diseases, including ten amino acid disorders (43.5%), eight organic acidaemias (34.8%) and five fatty acid oxidation defects (21.7%). In these infants, we clearly identified variants of disease-causing genes by next-generation sequencing (NGS). Most had two variants and others had one or three variants: 88% of gene variants were heterozygous and 12% were homozygous. There is a certain incidence of IEM in Jiangsu Province and it is necessary to carry out screening for 27 diseases. Meanwhile, NGS combined with TMS offers an enhanced plan for NBS, for IEM.